Naphthylacetic Acid and Tea Polyphenol Application Promote Biomass and Lipid Production of Nervonic Acid-Producing Microalgae - Xu, Feng; Fan, Yong; Miao, Fuhong; Hu, Guang-Rong; Sun, Juan; Yang, Guofeng; Li, Fu-Li (Frontiers in Plant Science, 2018)
Mychonastes afer HSO-3-1 is a potential producer of nervonic acid, which could be accumulated to 2-3% of dry cell weight. Improving the productivity of nervonic acid is critical to promote the commercialization of this product. In this study, 1-naphthylacetic acid (NAA) and tea polyphenol (TP) were selected as bioactive additives to stimulate the growth of M. afer. Supplementing NAA in the early growth stage and TP in the middle and late growth stage led to improved lipid accumulation in M. afer. The cultures supplemented with TP at the late growth stage maintained higher photosynthetic efficiency than the control groups without TP. Furthermore, the intracellular reactive oxygen species (ROS) accumulations in M. afer supplemented with 500 mg/L of TP was 63% lower than the control group. A linear relationship (R2=0.899) between the values of Fv/Fm and ROS accumulation was established. We hypothesize supplement of bioactive additives at different growth stage could promote the cell growth rate and nervonic acid productivity of M. afer by retrieving intracellular ROS level. Further analysis of photosynthetic system II (PSII) protein in M. afer cultured in presence of NAA and TP indicated the levels of D1 and D2 proteins, the core skeleton proteins of PSII, showed 33.3% and 25.6% higher than the control group. CP43 protein, a critical module in PSII repair cycle, decreased significantly. These implied that TP possesses the function of slowing down the damage of PSII by scavenging excess intracellular ROS.